Detection and identifcation of adherence genes of intestinal-origin Lactobacillus and Pediococcus strains grown on gastric mucin in vitro - W. Widodo; Sri Lestari; Widya Asmara (Indonesian Journal of Biotechnology, 2015)
One of the primary selection criteria for potential probiotics is the ability to adhere to the host gastrointestinal tract. This study evaluated the in vitro adhesion ability on gastric mucin of two Lactobacillus casei strains (AP and AG) and two Pediococcus acidilactici strains (BE and BK), and identifed the corresponding genes responsible for adherence. Adhesion assays were performed in 96-well polystyrene microtiter plates using gastric mucin from porcine stomach as the matrix. An in vitro study on gastric mucin revealed that lactobacilli had a greater adherence ability compared with pediococci strains. The potential adherence genes were investigated using polymerase chain reaction (PCR) technology. Using specifc primers, PCR studies amplifed 150 base pairs of a potential mub gene and 161 base pairs of a potential ef-Tu gene, but no amplifed bands for potential map and bac genes were obtained. Sequence comparisons showed that the 150 and 161 amplifed base pairs were respectively homologous to the mub of Pediococcus acidilactici and ef-Tu genes of Lactobacillus paracasei. We concluded that the adherence ability of two strains of Lactobacillus casei (AP and AG) and two strains of Pediococcus acidilactici (BE and BK) on gastric mucin is in accordance with the presence of ef-Tu and mub genes. High level attachment in lactobacilli is likely to correlate with the ef-Tu gene, which is a lactobacilli-specifc adhesive gene.